Does sex influence intraspecific aggression and dominance in Nile tilapia juveniles? - Pinho-Neto, Candido Ferreira [UNESP]; Miyai, Caio Akira [UNESP]; Carretero Sanches, Fabio Henrique [UNESP]; Giaquinto, Percilia Cardoso [UNESP]; Delicio, Helton Carlos [UNESP]; Gil Barcellos, Leonardo Jose; Volpato, Gilson Luiz [UNESP]; Barreto, Rodrigo Egydio [UNESP] (Elsevier B.V., 2014)
Although sex of mature fish is known to influence aggression, this issue has so far been neglected in juveniles. Here, we tested this sex effect and showed that it does not significantly affect intraspecific aggression in juveniles of the cichlid Nile tilapia. To reach this conclusion, we measured the latency period before onset of confrontation, the frequency and types of aggressive interactions, the duration of a dispute, and the probability of becoming dominant. This was done on pairs of Nile tilapia that varied by sex: females x females, males x males, and females x males. In a double blind approach, after pairing, the sex of each individual was histologically verified and contrasted with behavioral data. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Agonistic behavior; Aggression; Fighting; Males; Females; Sexual selection